Generalised Tapped Inductor Switcher (GTIS) approach to modelling of high‐order converters. Issue 4 (30th December 2020) - Yao, Jia; Ping, Jiang; Zheng, Kaisheng; Abramovitz, Alexander
Abstract: A generalized modelling technique suited to integrated and high order Pulse‐Width‐Modulation (PWM) topologies is studied and proposed here. Most integrated converters have their switches shared by more than one inductive element. The proposed generalised tapped inductor switcher model takes full account of the properties of the shared switcher assembly and so extends the capabilities of the earlier tapped inductor switcher model. The proposed generalised tapped inductor switcher can accommodate both voltage and current switched inputs and thus can model a wide range of high‐order PWM topologies. The topology of the GTIS block is proposed and its static and small‐signal models are derived. The proposed approach is illustrated by analysing a tapped inductor Single Eneded Primary Inductor converter. The validity of the proposed approach is verified by comparison of the theoretical, simulated and experimental results.